Interfacial Reviving of the Degraded LiNi0.8Co0.1Mn0.1O2 Cathode by LiPO3 Repair Strategy. Issue 16 (7th March 2022) - Feng, Ze; Zhang, Shan; Huang, Xiaobing; Ren, Yurong; Sun, Dan; Tang, Yougen; Yan, Qunxuan; Wang, Haiyan
Abstract: Nickel‐rich cathode materials, owing to their high energy density and low cost, are considered to be one of the cathodes with the most potential in next‐generation lithium‐ion batteries. Unfortunately, this kind of cathode with highly active surface is easy to react with H2 O and CO2 when exposed to ambient air, resulting in the formation of lithium impurities and interfacial phase transition as well as deterioration of the electrochemical properties. In this work, the evolution mechanism of the structure and interface of LiNi0.8 Co0.1 Mn0.1 O2 during air‐exposure is systematically investigated. Furthermore, a facile reviving strategy is proposed to restore the degraded LiNi0.8 Co0.1 Mn0.1 O2 by using LiPO3 as the repair agent. The lithium impurities on the surface of the degraded sample can transform into the repair/coating layer, and part of the rock salt phase on the subsurface can revive to layered phase after repair heat treatment. As a result, the optimized cathode delivers an initial discharge capacity of 198.3 mAh g −1 at 0.1C and a capacity retention of 85.5% after 50 cycles. Although slightly lower than the bare sample (201 mAh g −1 and 88%), they are obviously higher than the exposed samples (166.5 mAh g −1 and 40.4%). The regenerated electrochemical properties should be attributed to the multifunctional repair layer that can efficiently reduce the surface lithium impurities, prevent the corrosion of electrolyte, and improve the interfacial Li + diffusion kinetics. This work can effectively reduce the waste of the degraded Ni‐rich ternary materials and realize the transformation of "waste" into wealth. Abstract : Lithium metaphosphate is proposed to modify the degraded Ni‐rich cathodes. The detrimental lithium impurities on the surface can be converted into a uniform multifunctional repair/coating layer of Li3 PO4 ‐LiPO3, and part of the rock‐salt phase can be restored to layered phase. This work provides a facile and low‐cost surface engineering strategy for reviving the degraded Ni‐rich cathodes.